"Sleep is on the back burner": Working students and sleep. Issue 2 (1st June 2017) - Barone, T. Lynne
Abstract: The current study examines on a potential high-risk sleep loss population: working students at a metropolitan university in a mid-sized Midwestern city in the United States. Open-ended interviews with nineteen working university students provide insight into their beliefs and behaviors regarding how they think about and "do" work, attend university and sleep. Sleep diaries provide information on perceived sleep duration, latency and quality. While students value sleep and recognize the connection between sleep loss and ill health, they accept tiredness as "normal" for their situation. For many students sleep is the one demand that can be "put off", in the struggle to balance work, school and family demands, "until the bill comes due" when they fall ill. Exchanging sleep loss for educational progress is explored through "health capital" as part of a human capital conceptual framework.